Pengaruh Stres Kerja, Beban Kerja dan Kompensasi terhadap Kinerja Guru SMK Negeri 2 Purbalingga - Rissa Syabrina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Vocational High School 2 Purbalingga will continue to face challenges related to teacher performance in 2024. Based on pre-research results and the data obtained, a shortage of teaching staff has been identified, leading to excessive teaching loads and hours, job stress, and dissatisfaction among some teachers with their compensation. This study aims to determine the extent to which job stress, workload, and compensation influence teacher performance at Vocational High School 2 Purbalingga. This study used a quantitative method with a survey approach. The population in this study was all 84 teachers, all of whom were sampled using a saturated sampling technique. Data processing was performed using SPSS version 25. The results showed that job stress had no effect on teacher performance, while workload and compensation had a significant effect. Simultaneously, job stress, workload, and compensation influenced teacher performance. The coefficient of determination value of 0.451 indicates that these three variables influence teacher performance by 45.1%, while the remaining 54.9% is influenced by other factors not examined in this study. Therefore, it is recommended that the school increase the number of teaching staff to reduce excessive teacher workload